Dilute Ionic Liquids Pretreatment of Palm Empty Bunch and Its Impact to Produce Bioethanol - Arianie, Lucy; Pebriyana, Utin Dewi; Yudiansyah, Yudiansyah; Idiawati, Nora; Wahyuningrum, Deana (Chemistry Department, The University of Brawijaya, 2014)
Ethanol production through ionic liquids pretreatment of palm empty bunch (PEB) was carried out. This research aims to investigate impact of ionic liquids synthetic i.e 1-butyl-3-methyl imidazoliumbromide or [BMIM]bromide toward celluloseâ€™s palm empty bunch and convert its cellulose into bioethanol. Ionic liquid was synthesizedÂ through reflux and microwave assisted synthesis methods. Research investigation showed that microwave assisted synthesis produce [BMIM]bromide 90% faster than reflux method. The characterization of synthesized product using FTIR, 1H-NMR, 13C-NMR and LC-MS showed that these reactions have been carried out successfully. Scanning electron microscope figure out changes morphological surface of palm empty bunch caused by ionic liquid pretreatment. Crystallinity index of PEB milled and cellulose of PEFB after [BMIM]bromide dissolution were identified using comparison of PEB FTIR spectrum. Cellulose without dilute [BMIM]bromide have higher LOI number than cellulose after [BMIM]bromide dissolution. It indicated that a large part of cellulose after dissolution has been changed into amorf. Hydrolysis residue of palm empty bunch hydrolyzed by sulfuric acids 5%, 100 0C for 5 hours and produce 685 ppm of reducing sugar. Simultaneous Saccharification and Fermentation using Trichoderma viride and Saccharomyce cerevisiaeÂ for 5 days produce 0,69% of bioethanol.